Oxygen for the Newborn: Friend or Foe? - Serafina Perrone; Sara Manti; Chiara Petrolini; Valentina Giovanna Dell'Orto; Giovanni Boscarino; Chiara Ceccotti; Mattia Bertini; Giuseppe Buonocore; Susanna Maria Roberta Esposito; Eloisa Gitto (MDPI AG, 2023)
Oxygen supplementation is widely used in neonatal care, however, it can also cause toxic effects if not used properly. Therefore, it appears crucial to find a balance in oxygen administration to avoid damage as a consequence of its insufficient or excessive use. Oxygen toxicity is mainly due to the production of oxygen radicals, molecules normally produced in humans and involved in a myriad of physiological reactions. In the neonatal period, an imbalance between oxidants and antioxidant defenses, the so-called oxidative stress, might occur, causing severe pathological consequences. In this review, we focus on the mechanisms of the production of oxygen radicals and their physiological functions in determining a set of diseases grouped together as "free radical diseases in the neonate". In addition, we describe the evolution of the oxygenation target recommendations during neonatal resuscitation and post-stabilization phases with the aim to define the best oxygen administration according to the newest evidence.